Optimalisasi Media Youtube Sebagai Media Pembelajaran Daring - Unik Hanifah Salsabila; Nanik Rahmanti; Istiani Nur Kasanah; Dian Sidik Kurniawan; hening kusumaningrum (STAI Terpadu Yogyakarta, 2022)
Youtube is a media that can be accessed using the internet network that can be used to share and access various videos. The existence of the COVID-19 pandemic requires a change in all learning strategies. So that by using YouTube media, it is hoped that students will be able to understand the material taught by educators. Educators must also meet the target in teaching so that it is expected to make it easier for educators to teach and achieve these learning targets. Mastery of technology owned by educators is also a challenge. So that the use of YouTube media is expected to be a solution or alternative in making it easier for educators to stabilize the learning process. Based on the background above, it can be concluded that the problem formulation is how to use YouTube as a learning media, what are the obstacles and solutions in the use of YouTube learning media and what are the advantages and disadvantages of using YouTube learning media. This journal uses a qualitative method with an analytical descriptive model. Which will discuss the use of YouTube media in the learning process.